Determinants of change and household responses to food insecurity: Empirical evidence from Nigeria - Edeh, Hyacinth O.; Gyimah-Brempong, Kwabena (Academic Journals, 2015)
Limited economic and physical capacities as well as environmental and economic shocks have constrained the ability of many Nigerian households to feed themselves adequately. This has resulted in food shortages; and they had to adopt various consumption-related strategies to mitigate the effect of the shortfalls. Using the 2010/2011 Nigeria Living Standards Measurement Study-Integrated Surveys on Agriculture data and the reduced consumption coping strategy index (RCCSI), this paper examined the determinants of change in food (in)security of Nigerian households in the two major farming periods. Results showed that there were significant differences in the food insecurity status of households in the two periods. The likelihood of change in the food security status were determined by sex of the household head, farmland holdings, nature of livelihood, shocks associated with land loss, and climate change events. Coping strategies in the two periods were dietary change and rationing strategies. However, the frequency of use of these strategies was higher in the post-planting period and more among female-headed households. The use of high-yielding climate-resistant crops and reduction in post-harvest losses through processing and improved storage facilities were advocated.